2019
DOI: 10.1002/joa3.12153
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of CRT programming using non‐invasive electrocardiographic imaging to assess the acute electrical effects of multipoint pacing

Abstract: Aim Quadripolar lead technology and multi‐point pacing ( MPP ) are important clinical adjuncts in cardiac resynchronization therapy ( CRT ) pacing aimed at reducing the rate of non‐response to therapy. Mixed results have been achieved using MPP and it is critical to identify which patients require this approach and how to configure their MPP stimulation, in order to achieve optimal electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…[ 19 ] The potential of ECGI activation maps for detection of the best configuration of multi-polar pacing was demonstrated in a pilot study with five patients. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] The potential of ECGI activation maps for detection of the best configuration of multi-polar pacing was demonstrated in a pilot study with five patients. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…For delivering MPP from a single quadripolar LV lead, multiple studies showed immediate improvement of electrical synchrony and hemodynamic response compared to BiV. 9,22 Pacing from two electrodes with large anatomical spacing resulted in greatest benefits compared to other MPP pacing configurations during a long-term follow-up. 10,23,24 Our results are in line with this data as QRSd was significantly shortened by MPP compared to BiV alone.…”
Section: Discussionmentioning
confidence: 99%
“…SyncAV Recent studies report an improvement of acute electrical synchrony and improved reverse remodeling during follow-up compared to conventional biventricular pacing. 9,10 Whether combination of SyncAV and MPP leads to a greater improvement of electrical synchrony remains unknown. In the present work, we assessed whether using the novel technologies improves electrical synchrony in both newly and previously implanted CRT devices.…”
Section: Introductionmentioning
confidence: 99%
“…Для многополюсной стимуляции используют два катода, полученных с помощью четырех электродов [30][31][32]. При сравнении с бивентрикулярной стимуляцией установлено улучшение сократимости, гемодинамики и синхронизации между желудочками [33][34][35][36][37][38][39], особенно у пациентов, которые не склонны отвечать на терапию с помощью стандартной СРТ, то есть имеющих узкий комплекс QRS, атипичную морфологию блокады левой ножки пучка Гиса, I тип активации ЛЖ и рубцы миокарда [40][41][42]. Таким образом, в последнее время появляются сведения о многополюсной стимуляции ЛЖ при СРТ, которая вероятно увеличит количество пациентов, ответивших на лечение (респондеров).…”
Section: Discussionunclassified